The success of go-pay financial technology service adoption - Nurherwening, Aris; Dari, Aulia Wulan; Urumsah, Dekar; Wibowo, Hari Tri (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2021)
Go-Pay is one of the popular FinTech services in Indonesia. This research aims to identify the Go-Pay service's impact on net benefits influenced by perceived usefulness, perceived ease of use, comfort, information quality, security, trust, and internet connection quality. This research used a quantitative method to collect 220 data by distributing a questionnaire through Google Form and analyzing them using SmartPLS 3.3. The result shows that comfort, information quality, and perceived ease of use significantly impact the perceived usefulness. In contrast, internet connection quality, trust and security were proved to have no significant impact on the perceived usefulness. Comfort, information quality, trust, internet connection quality had a significant impact on the perceived ease of use. However, security had no significant impact on perceived ease of use. Perceived usefulness and perceived ease of use had a significant impact on net benefits. This research can use as a decision-making strategy for Go-Jek as a company concerning the success of Go-Pay service.